Isolation and molecular identification of dengue and chikungunya viruses from field-collected aedes mosquitoes in Kota Bharu areas, Kelantan - Jusoh, Tuan Nur Akmalina Mat (2024)
Dengue and chikungunya infections have been a major public health threat in Malaysia with a significant number of deaths reported every year. Both diseases are transmitted mainly by Ae. aegypti and Ae. albopictus and cause a wide range of clinical manifestations from mild fever to severe fatal cases. This study aimed to investigate the circulating CHIKV and DENV serotypes from field-collected adult Aedes mosquitoes in the Kota Bharu area. A total of 114 mosquito pools (610) comprising 30 pools (69 male and 40 female mosquitoes) of Ae. aegypti and 84 pools (208 male and 293 female) of Ae. albopictus were collected at DENV outbreak localities in Kota Bharu from January to August 2019 using a sweep net and sticky ovitrap. Virus isolation was carried out in C6/36 cells and the presence of DENV was confirmed using dengue non-structural (NS1) antigen and DENV multiplex reverse transcriptase polymerase chain reaction (RT-PCR) assay. On the other hand, a one-step RT-PCR assay was performed to detect CHIKV. Badang locality showed the highest population of Ae. albopictus while no collection from the Panchor locality. Most of Ae. aegypti was recorded at Kampung Demit Sungai. For DENV multiplex RT-PCR assay, the optimum condition of annealing temperature was 60ºC, 0.1 µM (DENV 1 and DENV 2) and 0.2 µM (DENV 3 and DENV 4) for primer concentration. Of 91, four mosquito pools were positive for dengue NS1 antigen by ELISA comprising two pools (2.2%) of male Ae. albopictus (Pulau Melaka and Kubang Siput locality) and two pools (2.2%) of Ae. aegypti (Kampung Demit Sungai). DENV 1 was detected in one pool (0.9%) of female Ae. albopictus among 114 tested Aedes pools. Two pools (1.7%) from male Ae. aegypti and Ae. albopictus were positive with double serotypes, DENV 1 and DENV 2 (Pulau Melaka). Most of the positive mosquito pools by dengue NS1 antigen were negative by RT-PCR except one pool of male Ae. albopictus from Pulau Melaka. However, no mosquito pool was positive for CHIKV in the study. The findings revealed that DENV 1 and DENV 2 were the current circulating virus in the study area. In addition, Ae. albopictus was the predominant species in the Kota Bharu area. The presence of DENV and the main vectors of DENV in Kota Bharu are pertinent indicators of the need to improve vector controls to reduce arbovirus infections among people in the localities.